2013
DOI: 10.1093/hmg/ddt338
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mitochondrial peptidase Clpp leads to infertility, hearing loss plus growth retardation via accumulation of CLPX, mtDNA and inflammatory factors

Abstract: The caseinolytic peptidase P (CLPP) is conserved from bacteria to humans. In the mitochondrial matrix, it multimerizes and forms a macromolecular proteasome-like cylinder together with the chaperone CLPX. In spite of a known relevance for the mitochondrial unfolded protein response, its substrates and tissue-specific roles are unclear in mammals. Recessive CLPP mutations were recently observed in the human Perrault variant of ovarian failure and sensorineural hearing loss. Here, a first characterization of CLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
260
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(290 citation statements)
references
References 113 publications
26
260
4
Order By: Relevance
“…Serum glucose, cholesterol, and phospholipids showed no significant difference between Clpp ‐deficient and WT mice at any time point, while triglycerides were significantly lower in 9 months old Clpp −/− mice ( p  <   0.01; Supporting Information Figure S2). To confirm the reported infertility of Clpp −/− female mice (Gispert et al., 2013), we conducted a continuous mating study using sexually mature female mice ( n  = 5 for each genotype) and WT male mice of proven fertility. After 12 weeks of mating, there were no pregnancies or deliveries observed in Clpp −/− female mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum glucose, cholesterol, and phospholipids showed no significant difference between Clpp ‐deficient and WT mice at any time point, while triglycerides were significantly lower in 9 months old Clpp −/− mice ( p  <   0.01; Supporting Information Figure S2). To confirm the reported infertility of Clpp −/− female mice (Gispert et al., 2013), we conducted a continuous mating study using sexually mature female mice ( n  = 5 for each genotype) and WT male mice of proven fertility. After 12 weeks of mating, there were no pregnancies or deliveries observed in Clpp −/− female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional activation of mtUPR genes and translational suppression seem to be mediated by two parallel mechanisms, both requiring CLPP (Aldridge et al., 2007; Benedetti et al., 2006; Haynes et al., 2007; Zhao et al., 2002) and reviewed in (Jensen & Jasper, 2014; Schulz & Haynes, 2015). It is important that, recessive Clpp mutations have been identified in the human Perrault variant of ovarian failure and sensorineural hearing loss (Jenkinson et al., 2013), and global germline Clpp knockout mice display auditory deficits and complete female and male infertility, in addition to reduced pre/postnatal survival and marked ubiquitous growth retardation (Gispert et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological importance of these proteolytic complexes is reflected in their requirement for the viability and/or virulence of some bacteria and the observation that loss-of-function mutations in mammals are linked to developmental defects and disease (2)(3)(4)(5)(6)(7)(8). Most well-characterized ClpP enzymes come from organisms that have a single clpP gene and consist of identical heptameric rings, which stack face-to-face to enclose a degradation chamber in which 14 active sites mediate peptide-bond hydrolysis (1,9,10).…”
mentioning
confidence: 99%
“…Based on its close relation to the bacterial protease system, mtClpP is assumed to be involved in PQC functions in the matrix although no specific substrates are known so far. Very recently, a knockout model of mtClpP in mice was published, exhibiting pronounced growth retardation and failure of certain organ functions [107]. Another recent finding revealed that a knockdown of the corresponding chaperone component, mtClpX, resulted in alterations of mitochondrial nucleoid structure in human cells [108].…”
Section: Clppmentioning
confidence: 99%